PERLINDUNGAN HUKUM FENOMENA CITAYAM FASHION WEEK DALAM KEKAYAAN INTELEKTUAL KOMUNAL - Rizka Nabila, (2023)
The development of the digital era has made communication technology fast in disseminating information through social media. In 2022, there was a phenomenon where there was a change in the culture of punk kids who are known to have negative habits around Sudirman, creating a positive activity, namely Citayam Fashion Week, which was spread by these teenagers through social media and became viral. In its aim to channel expression in public spaces, Citayam Fashion Week teenagers need legal protection. This study uses an Empirical Juridical and Normative Juridical Approach. The specification of the research is in the form of analytical descriptive. The method of collecting data is through library research (Library Research), namely studying and studying legal literature. The statutory approach and the case approach are used in this study. The data analysis technique used is descriptive analysis technique in the form of a qualitative analysis method. Citayam Fashion Week can be recognized by the public because of the rapid flow of globalization in information technology so that something published on social media can spread quickly. Legal protection that can be obtained is Repressive and Preventive legal protection. The other forms of protection for Communal Intellectual Property are preserving, documenting, maintaining, preventing rights violations and coaching.